A Christian Pluralistic Hypothesis: To Bonhoeffer and beyond—A World Christianity - Gorsuch, Greg (Religions, 2024)
This essay investigates Bonhoeffer’s undeveloped concept of “Unconscious Christianity” and how a protracted understanding of his religionless Christianity in a culture “come of age” points to a viable Christian pluralistic hypothesis—how Christ and the Spirit are redemptively active outside the church. Bonhoeffer’s living faith action transcends his theology, revealing unconscious dynamics within our interactions that reveal antecedent relational dynamics that open to the redemptive process, which transcend but do not obviate the cognitive elements of faith. New scriptural themes and concepts of relationality and perichoretic metaphysics bring greater biblical coherence and meaning to one particular biblical passage that has apparently remained meaningless (Matt 12:32). This new meaning and coherence within the scriptures radically alter Christianity’s relationship to the outside world and transforms our understanding of the Great Commission.